Les normes de prononciation du français: Une étude perceptive panfrancophone - Chalier, Marc (2021)
This book focusses on the plurality of pronunciation norms in French. The traditional Parisian norm is compared to the potential regional norms of Québec and French-speaking Switzerland based on the productions of professional model speakers as well as norm-related perceptions, representations and attitudes of non-expert informants. The results show a bicentric tendency, with a respectively dominant norm in Europe (Paris) and North America (Québec).